(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Building arguments for academic writing, such as constructing justification for a research proposal, is regarded a complex task. Moreover, it is believed that male and female authors use and produce the language differently, including perhaps providing thesis and arguments for research. Extensive research on rhetorical analysis of students’ theses has been widely conducted; however, little we know the way they state their claims from gender perspectives. To fill the void, this study aims to explore how Indonesian male and female authors construct and state their arguments in Introduction section for justifying their research from the perspectives of argumentation ability, underpinned by the concepts of transitivity system of SFL approach. Informed by qualitative descriptive research paradigm particularly text analysis, ten Introduction sections from selected English thesis proposals written by male and female authors at a university in Banten Province, Indonesia were subject to analyze. The finding of the research shows that either male students or female students expressed their arguments of their research topic and justification in almost similar fashion. The most frequent processes over the clauses were material process, relational process (attributive and identifying), and mental process (male: 59%, 20%, 11%; female: 49%, 20%, 14%). These findings underscore the common strategies employed by students, regardless of gender, in establishing their research objectives and setting the stage for their academic work. Such insights can be of significance for educators and researchers aiming to guide students in optimizing their academic writing skills, particularly in crafting compelling Introduction sections for thesis proposals.